STUDI IDENTIFIKASI PENGELOLAAN AIR LIMBAH DOMESTIK di KECAMATAN MIJEN, GUNUNGPATI, GAJAHMUNGKUR dan SEMARANG SELATAN KOTA SEMARANG - Alfiza Fahmi; Wiharyanto Oktiawan; Mochtar Hadiwidodo (Jurnal Teknik Lingkungan, 2013)
Sanitation refers to the hygienic and proper management, collection, disposal or reuse of human excreta (feces and urine) and community liquid wastes to safeguard the health of individuals and communities. Sanitation have three primary objectives:Improving health conditions, promoting dignity of living or enhanced quality of life,  and protecting the environment. The combined positive eﬀects of these conditions lead to wider economic beneﬁt. One of sanitation component is domestic wastewater which is in fact haven’t use the proper management . Proper management can be decided by assessing current situation (sourced by primary and secondary data), gap analysis based on three aspects which is institutional aspects, technical aspects, financing aspects, legal aspects and community participation. This study identification focused on determining domestic wastewater processing system based on population density, the area physical condition, the source of water used, and the ability to finance. Whereas scope area of this identification study is Mijen, Gunungpati, Gajahmungkur and South Semarang at Semarang city. Mijen and Gunungpati has similarity at population density which is less than 150 people per ha and the area physical condition such as high permeability, ground water depth >50 meters, dominated by 2-15% slope, and also from the financial side that  range income level 1,5-3 million rupiah is still suitable for septic tank as it’s technology an on site system as its alternative system. In the other side, Gajahmungkur and South Semarang also has similarity at water used sourced which is 72% and 75%  respondent use PDAM as primary source and generally has middle class of  permeability. Both of this sub district also has population density more than 150 people per ha and the area dominated by 2-15% slope range which is all of those factor suitable for sewerage conventional as its technology.This study help the reader to make informed about the proper prossesing system of each study area and furthermore to achieve sanitation primary objectives.